Type-2 Cytokines Promote the Secretion of the Eosinophil–Attractant CCL26 by Intestinal Epithelial Cells in Food-Sensitized Patients - Vaccaro, Julián; Canziani, Karina Eva; Guzmán, Luciana; Bernedo, Viviana; García, Marcela; Altamirano, Eugenia Margarita; Feregotti, Emanuel; Curciarello, Renata; Muglia, Cecilia Isabel; Docena, Guillermo Horacio (Frontiers in Immunology, 2022)
Several inflammatory processes of the bowel are characterized by an accumulation of eosinophils at inflammation sites. The mechanisms that govern mucosal infiltration with eosinophils are not fully understood. In this work, we studied the colorectal polyp-confined tissue containing eosinophils and we hypothesized that intestinal epithelial cells are the cell source of eotaxin-3, a potent chemoattractant for eosinophils. We analyzed colorectal polyps (n=50) from pediatric patients with rectal bleeding by H&E staining and eosin staining, and different pro-inflammatory cytokines were assessed by RT-qPCR and ELISA. IgE and CCL26 were investigated by RT-qPCR, ELISA and confocal microscopy. Finally, the intracellular signaling pathway that mediates the CCL26 production was analyzed using a kinase array and immunoblotting in human intestinal Caco-2 cell line. We found a dense cell agglomeration within the polyps, with a significantly higher frequency of eosinophils than in control adjacent tissue. IL-4 and IL-13 were significantly up-regulated in polyps and CCL26 was elevated in the epithelial compartment. Experiments with Caco-2 cells showed that the type-2 cytokineIL-13 increased STAT3 and STAT6 phosphorylation and eotaxin-3 secretion. The addition of the blocking antibodies Dupilumab or Ruxonitinib to the cytokine-stimulated Caco-2 cells diminished the CCL26 secretion to basal levels in a dose-dependent manner. In conclusion, our findings demonstrate a high frequency of eosinophils, and elevated levels of type-2 cytokines and eotaxin-3 in the inflammatory stroma of colorectal polyps from pediatric patients. Polyp epithelial cells showed to be the main cell source of CCL26, and IL-13 was the main trigger of this chemokine through the activation of the STAT3/STAT6/JAK1-2 pathway. We suggest that the epithelial compartment actively participates in the recruitment of eosinophils to the colonic polyp-confined inflammatory environment.